PENYESUAIAN DIRI DAN KONFORMITAS TERHADAP ETOS BELAJAR MAHASISWA DALAM PEMBELAJARAN DARING - Mutia Mawardah; Fathulul Amri Effendi (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2022)
This study aims to determine the relationship between self-adjustment and peer conformity with students' learning ethos in bold learning. The hypothesis proposed in this research is that there is a relationship between self-adjustment and peer conformity with students' learning ethos in bold learning, secondly there is a relationship between self-adjustment and students' learning ethos in courageous learning, and so on there is a relationship between peer conformity and student learning ethos in dare to learn. The population of this study were students at Bina Darma University Palembang with a total of 320 active students who were determined by adapting Isaac and Michael's table based on an error rate of 5% with the distribution of test subjects to 200 students while the remaining 120 were as samples in the study. Data collection was obtained by using a probability sampling technique, namely simple random sampling. It was stated simply because in selecting sample members from the population it was carried out randomly without regard to the existing strata in the population. The results of multiple regression research using the SPSS program show a correlation coefficient (r) of 0.915, a coefficient of determination (R Square) of 0.837 and a value of p = 0.000 p <0.05. The results of the analysis show that there is a very significant relationship between self-adjustment and student learning ethos in online learning.